Chemical composition and fermentative parameters of elephant grass and sugar-cane silage treated with additives Composição química e parâmetros fermentativos de silagens de capim-elefante e cana-de-açúcar tratadas com aditivos - Elson Martins Coelho; Maria da Graça Morais; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Alexandre Menezes Dias (Revista Brasileira de Saúde e Produção Animal, 2010)
It was aimed to evaluate the effect of different additives in the elephant-grass (Pennisetum purpureum Schum.) and sugar-cane (Saccharum officinarum L.), before and after the ensilage, through fermentation and chemical composition measures. The roughages were ensiled in PVC laboratory silos, with three for treatment, totalizing 24 microsilos for specie, in a completely randomized design. The treatments were control (without additive), corn meal, common salt, urea, acetic acid, formic acid, microbial inoculant and dried molasses. Samples were taken before and after 35 days of ensilage. Dry matter, crude protein and ammonia-N contents, pH and buffering capacity values and dry matter losses were analyzed. The elephant-grass presented satisfactory results for conservation in the silage form, and it was not necessary the use of additives. The sugar-cane presented satisfactory results for conservation in the silage form. The corn meal was the additive that promoted best fermentation pattern and smaller losses, as an option in the making of the sugar-cane silage. Objetivou-se avaliar o efeito de aditivos no capim-elefante (Pennisetum purpureum Schum.) e na cana-de-açúcar (Saccharum officinarum L.), antes e após a ensilagem, através de medidas de fermentação e composição química. As forragens foram ensiladas em silos laboratoriais de PVC, com três unidades por tratamento, num total de 24 microsilos por espécie forrageira, em delineamento inteiramente casualizado. Os tratamentos consistiram em controle (sem aditivo), fubá, cloreto de sódio, ureia, ácido acético, ácido fórmico, inoculante microbiano e melaço em pó. Amostras foram tomadas antes e após 35 dias de ensilagem, de modo que foram analisados os teores de matéria seca (MS), proteína bruta e nitrogênio amoniacal, os valores de pH e capacidade tamponante, além das perdas de matéria seca. O capim-elefante apresentou resultados satisfatórios para conservação na forma de silagem, sem que fosse necessário o uso de aditivos. A cana-de-açúcar apresentou resultados satisfatórios para conservação na forma de silagem. O fubá foi o aditivo que promoveu melhor padrão de fermentação e menores perdas como uma opção na confecção da silagem de cana-de-açúcar.